2021
DOI: 10.1002/adma.202107843
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Controlled Nucleation and Shaping of Self‐Assembling Nanocomposites

Abstract: Controlling self‐assembly of nanocomposites is a fundamental challenge with exciting implications for next‐generation advanced functional materials. Precursors for composites can be generated photochemically, but limited insight in the underlying processes has hindered precise hands‐on guidance. In this study, light‐controlled nucleation and growth is demonstrated for self‐assembling composites according to precise user‐defined designs. Carbonate is generated photochemically with UV light to steer the precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…We foresee that these insights may directly impact our ability to shape chemical compositions according to an exact design by first programming a desired shape and subsequently customizing the chemical composition. As a first step, we recently demonstrated that photogeneration of carbonate enables light-controlled nucleation and sculpting of these composites . The next step toward this ambitious goal will be to gain complete hands-on control over the self-assembly process of the nanocomposite in three dimensions, thus opening new routes toward rationally designed functional structures for catalysis, optics, and photovoltaics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We foresee that these insights may directly impact our ability to shape chemical compositions according to an exact design by first programming a desired shape and subsequently customizing the chemical composition. As a first step, we recently demonstrated that photogeneration of carbonate enables light-controlled nucleation and sculpting of these composites . The next step toward this ambitious goal will be to gain complete hands-on control over the self-assembly process of the nanocomposite in three dimensions, thus opening new routes toward rationally designed functional structures for catalysis, optics, and photovoltaics.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, we recently demonstrated that photogeneration of carbonate enables light-controlled nucleation and sculpting of these composites. 39 The next step toward this ambitious goal will be to gain complete hands-on control over the self-assembly process of the nanocomposite in three dimensions, thus opening new routes toward rationally designed functional structures for catalysis, optics, and photovoltaics.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Changing the environmental conditions by e.g. changing the CO 2 influx, or the local availability of CO 2 via a photochemical reaction, 71 allows modulating the local gradients around the growth front, and thereby switching between different types of structures that are co-precipitating over the course of the growth process. Finally, the structures produced this way can be modified via ion-exchange reactions ( Fig.…”
Section: Reaction–diffusion Systemsmentioning
confidence: 99%
“…In addition, local control over CO 2 concentrations using photodecarboxylation enables the steering of the self-organization process to yield metal carbonate silica nanocomposites according to exact user-defined light patterns. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary complexity of biomineralized architectures demonstrates the possibilities for organizing a limited number of simple minerals into a wide diversity of highly refined, multifunctional, three-dimensional (3D) shapes. Inspired by biomineralization processes, many synthetic self-organization strategies have been developed to produce artificial complexly shaped 3D architectures. , Already, a large diversity of intricately shaped 3D forms can be formed during the bioinspired coprecipitation of metal carbonate nanocrystals (MCO 3 , with M = Ba 2+ , Sr 2+ , or Ca 2+ ) and amorphous silica (SiO 2 ) (Figure A). ,, These bioinspired nanocomposites self-organize into highly complex, yet controllable, 3D shapes such as vases, stems, helices, and coral-like forms that can be further sculpted and patterned by modulating the global reaction conditions. In addition, local control over CO 2 concentrations using photodecarboxylation enables the steering of the self-organization process to yield metal carbonate silica nanocomposites according to exact user-defined light patterns …”
Section: Introductionmentioning
confidence: 99%